Surgical Outcome and Malignant Risk Factors in Patients With Thyroid Nodule Classified as Bethesda Category III - Huang, Jianhao; Shi, Hongyan; Song, Muye; Liang, Jinan; Zhang, Zhiyuan; Chen, Xiaohang; Liu, Yongchen; Wang, Sanming; Wu, Zeyu (Frontiers in Endocrinology, 2021)
Background Thyroid nodules are very common finding in the general population. Fine-needle aspiration (FNA) has recommended as the initial test for evaluation of thyroid nodules. The trend on reporting as AUS has been significantly increased, but the malignant risk is still controversial among different studies. The aim of this study is to investigating the malignancy risk of thyroid nodules reported as Bethesda category III (AUS/FLUS) on initial FNA. Method We reviewed 272 PTC patients with suspicious thyroid nodules who underwent fine-needle aspiration and received surgical treatment during 2019 to 2020. Results 110 (40.4%) patients were diagnosed with PTC. Multivariate analysis showed that microcalcification (P=0.037, OR =2.260, 95% CI: 1.051-4.860), Shape (P=0.003, OR =4.367, 95% CI: 1.629-11.705), Diameters (P=0.002, OR =0.278, 95% CI: 0.123-0.631), TGAb (P=0.002, OR =0.150, 95% CI: 0.046-0.494), A-TPO (P=0.009, OR =4.784, 95% CI: 1.486-15.401) and Nodule Goiter (P<0.001, OR =0.100, 95% CI: 0.046-0.217) were independent malignant risk factors in patients with thyroid nodule classified as Bethesda category III. Conclusion In this study, malignant risk factors in patients with thyroid nodule classified as Bethesda category III was significantly associated with preoperative serum TGAb, A-TPO, microcalcification, irregular shape and nodule diameters. Nodules with malignant factors should be carefully elevated, surgery may be the better option for those patients.